VMAT–SBRT planning based on an average intensity projection for lung tumors located in close proximity to the diaphragm: a phantom and clinical validity study - Ohira, Shingo (J Radiat Res, 2016)
The aim of the this study was to validate the use of an average intensity projection (AIP) for volumetric-modulated arc therapy for stereotactic body radiation therapy (VMAT–SBRT) planning for a moving lung tumor located near the diaphragm. VMAT–SBRT plans were created using AIPs reconstructed from 10 phases of 4DCT images that were acquired with a target phantom moving with amplitudes of 5, 10, 20 and 30 mm. To generate a 4D dose distribution, the static dose for each phase was recalculated and the doses were accumulated by using the phantom position known for each phase. For 10 patients with lung tumors, a deformable registration was used to generate 4D dose distributions. Doses to the target volume obtained from the AIP plan and the 4D plan were compared, as were the doses obtained from each plan to the organs at risk (OARs). In both phantom and clinical study, dose discrepancies for all parameters of the dose volume (D(min), D(99), D(max), D(1) and D(mean)) to the target were <3%. The discrepancies of D(max) for spinal cord, esophagus and heart were <1 Gy, and the discrepancy of V20 for lung tissue was <1%. However, for OARs with large respiratory motion, the discrepancy of the D(max) was as much as 9.6 Gy for liver and 5.7 Gy for stomach. Thus, AIP is clinically acceptable as a planning CT image for predicting 4D dose, but doses to the OARs with large respiratory motion were underestimated with the AIP approach.